If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(y+1)=3y+7
We move all terms to the left:
4(y+1)-(3y+7)=0
We multiply parentheses
4y-(3y+7)+4=0
We get rid of parentheses
4y-3y-7+4=0
We add all the numbers together, and all the variables
y-3=0
We move all terms containing y to the left, all other terms to the right
y=3
| 4−7w=16 | | 2+14x+11+3x=180 | | 7+2(5•3)=2r+5 | | -5=-4n+2 | | 3z=243 | | .5+x=1.5+x | | 4=x=-7 | | 24=-8-4x | | 2+14x+11x+3=180 | | 9x-162=90 | | -3.1=w/6+16.1 | | 5Xx+3=8Xx+12 | | 6x+32=68 | | 3x+70=360 | | 9x+162=90 | | 2x5x=-4 | | 2*p-10=p+20 | | 27-f=20 | | 61.8=6(m+3.4) | | 6-5k=-24 | | -6x+4/11=-4 | | –9.21−7.7f=–1.77−6.9f | | 6^x+9=27 | | (17/3a)-10=2/(3a) | | 2x5;x=-4 | | -29=-16+x | | 3x+6+5x-54=180 | | x^2+3x=10300 | | .3x+2(x−1)=9x+4 | | 26=-10+9p | | 690/a=6.9 | | -36=v-18 |